Spider venom-derived peptide JZTX-14 prevents migration and invasion of breast cancer cells via inhibition of sodium channels - Wu, Wenfang; Yin, Yuan; Feng, Peihao; Chen, Gong; Pan, Liangyu; Gu, Panyang; Zhou, Siqin; Lin, Fulong; Ji, Siyu; Zheng, Chunbing; Deng, Meichun (Frontiers in Pharmacology, 2023)
Nav1.5 channel is crucial for the proliferation and migration of breast cancer cells. In this study, we investigated the anticancer effect of JZTX-14, a natural peptide considered an effective antagonist of Nav1.5. First, we successfully isolated and purified the 31 amino acid peptide JZTX-14 containing three pairs of disulfide bonds from spider venom and synthesised JZTX-14 by solid phase synthesis. We then predicted their physiochemical properties and structures in the peptide database. Further, we investigated the effects of natural and synthetic JZTX-14 on the proliferation and migration of MDA-MB-231 breast cancer cells via modulation of sodium current through the Nav1.5 channel. The results showed that both synthetic and natural JZTX-14 inhibited Nav1.5 currents, indicating the successful synthesis of JZTX-14. However, JZTX-14 did not affect MDA-MB-231 cell proliferation but inhibited its migration. Transcriptome analysis revealed that JZTX-14 downregulated S100A4 and FBXO2 and upregulated SERPINB2 in MDA-MB-231 cells. Western blot analysis demonstrated an increased level of the epithelial marker, E-cadherin, and decreased levels of the mesenchymal markers, N-cadherin and vimentin, and matrix metalloproteinase (MMP2), indicating the possible underlying mechanism of the inhibition of MDA-MB-231 cell migration by JZTX-14. This study provides a new target for inhibiting breast cancer metastasis and identifies a potent natural peptide for treating TNBC.